Overweight in Boys With ADHD Is Related to Candidate Genes and Not to Deficits in Cognitive Functions. Issue 12 (October 2018) - Hanć, Tomasz; Dmitrzak-Węglarz, Monika; Borkowska, Aneta; Wolańczyk, Tomasz; Pytlińska, Natalia; Rybakowski, Filip; Słopień, Radosław; Słopień, Agnieszka
Objective: The aim of the study was to assess the relationship of overweight, the polymorphisms of selected candidate genes, and deficits in the executive functions among children with ADHD.Method: We examined 109 boys with ADHD aged between 7 and 17 years. The study indicated variants of 14 polymorphisms in eight candidate genes. We applied seven neuropsychological tests to evaluate the executive functions. Overweight was diagnosed on the basis of the guidelines of the International Obesity Task Force.Results: Analyses revealed significant association between DRD4 rs1800955, SNAP25 rs363039 and rs363043, 5HTR2A rs17288723, and overweight in boys with ADHD. There were no significant differences in the level of neuropsychological test results between patients with overweight and without overweight.Conclusion: Overweight in boys with ADHD is associated with polymorphisms in three candidate genes: DRD4, SNAP25, and 5HTR2A, but not through conditioning deficits in cognitive functions.